Evaluating the Impact of Wastewater Irrigation on Soil Health and Maize Productivity - Mubeen, Aniqa; Waseem Ur Rehman; Abdul Momin; Hayat, Maryam; Ullah, Ghazanfar; Iram, Adila; Naheed, Rafia; Irum, Ayesha; Sami Ullah (Indus Journal of Bioscience Research, 2024)
The increasing scarcity of freshwater resources necessitates the exploration of alternative water sources for agricultural irrigation. This study evaluates the impact of different water sources canal water, tubewell water, sewerage water, and industrial wastewater on soil health and maize productivity. Conducted over two growing seasons, the experiment was laid out in a randomized complete block design with four replications at research area of Ayub Agriculturte Research Institute, Faisalabad. Key soil physical properties, including bulk density, porosity, and infiltration rate, were assessed pre- and post-irrigation. Concurrently, maize growth parameters such as germination rate, plant height, biomass, and grain yield were meticulously recorded. The results indicated that soil irrigated with sewerage and industrial wastewater exhibited significant increases in bulk density and reductions in porosity and infiltration rates compared to canal and tubewell water. Despite these alterations in soil physical properties, maize irrigated with sewerage water showed a comparable growth pattern to that irrigated with canal and tubewell water, with no significant differences in germination rate or plant height. However, grain yield and biomass were significantly higher in plots irrigated with canal water, followed closely by tubewell water, sewerage water, and lastly, industrial wastewater. Industrial wastewater irrigation notably decreased soil health and maize productivity due to the presence of heavy metals and other pollutants. In contrast, sewerage water, while still inferior to canal and tubewell water, provided a viable alternative, maintaining acceptable soil health and maize yield levels. This study underscores the potential of using treated wastewater for irrigation in regions facing water scarcity, highlighting the need for stringent quality monitoring and treatment protocols to mitigate adverse effects on soil health and crop productivity.